PERILAKU INSTRUKTIF DALAM MENGOPTIMALISASI KERJA PEGAWAI - Dian Fitrian E.21111093 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
The focus of this research is directed at the behavior of instruction in optimizing the performance of employees. This study used a descriptive research model with data processing techniques of qualitative analysis. Research is located in the Natuna District Revenue Office uses data collection techniques such as observation, interview and documentation by means of a check list of data collection, interviews and document guidelines. The results of the data analysis showed that the elements of leadership in the Natuna District Revenue Office has implemented a leadership behavior instructive and cannot optimize employee performance. For that, we need to increase support and guidance to minimize, improve two-way communication and support of subordinates, optimizing participative leadership and discretionary behavior by distributing tasks according to the ability and expertise of subordinates. Keywords: Bureaucratic Work